Mica platelet-reinforced geopolymer composites - Keane, P.; Kutyla, G.; Wight, J.; Rickard, William; Kriven, W. (2017)
© 2017 by The American Ceramic Society. Composites of phlogopite mica platelets of composition KMg 3 AlSi 3 O 10 (F,OH) 2 dispersed in potassium-based potassium geopolymer were fabricated. The platelet additions of up to 25 wt% were achieved which increased the flexure strength and thermal conductivity of pure potassium-based geopolymer. A maximum 3-point flexure strength at room temperature was measured as 11.4 MPa with a standard deviation of 0.34 MPa for 25 wt% mica additions. Heat treatments caused chemical decomposition and water loss at temperatures up to 700 °C and eventual formation of glassy and crystalline leucite at 1000°C. A maximum post-treatment strength of 10.7 MPa with a standard deviation of 0.52 MPa was obtained for the 1000°C heat-treated samples. The thermal conductivity increased from 0.24 ± 0.000 W/mK for pure K-based geopolymer to 0.30 ± 0.008 W/mK, as a function of mica platelet additions up to 10 wt %.